Orientational glassification in fullerite C60 saturated with H2: photoluminescence studies - Zinoviev, P.V.; Zoryansky, V.N.; Silaeva, N.B.; Stetsenko, Yu.E.; Strzhemechny, M.A.; Yagotintsev, K.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
Using one-photon excitation we studied photoluminescence of C60 saturated with molecular hydrogen overa temperature range 10 to 230 K. Saturation of samples was done at a pressure of 30 atm and at temperatures low enough (T < 250 °C) to exclude chemical sorption. The samples were saturated during periods of varied duration τ to reach different occupancy levels. To check reliability of our luminescence results and interpretation, our spectra for pure C60 were compared with data known in the art, demonstrating good compatibility. The luminescence spectra were attributed according to the approach of Akimoto and Kan,no by separating total spectra in two components of different origin. The A-type spectra, which are associated with exciton transport to deep traps, above 70 K become prevail over the B-type emission. Until saturation times did not exceed a certain value (for one, 50 h for a saturation temperature of 200 °C) the integrated intensity I as a function of the temperature Tof luminescence measurements, I(T), remained at a constant level up to the orientational vitrification point of about 100 K and then went rather steeply down with increasing T. However, at longer τ the intensity I(Τ) persisted in constancy to higher T (the higher, the longer τ) and then dropped with increasing T. This finding made us to reexamine more closely the lattice parameter vs saturation time dependence for saturation temperatures 200 and 230 °C. As a result, additional evidence allowed us to infer that after completion of the single-molecule filling of O-voids (specifically, after roughly 50 h for Tsat = 200 °C) a slower process of double filling sets in. Double filling entails an anisotropic deformation of the octahedral cage, which modifies rotational dynamics stronger than single filling. Further, we argue that singlet exciton transport to traps (which is responsible for the A-type emission) can be crucially hampered by rotational jumps of one of the molecules over which a travellingexciton is spread. Such jumps break coherence and the exciton stops thereby increasing the probability of emissionless deactivation. If so, then the temperature, at which the rotational jumps occur sufficiently frequently, may be by inference considered the unfreezing point for the orientational glass state (essentially coinciding with the inverse critical point Tg where the rotational system freezes into the orientational glass). This treatment of Tg differs from that existing in the art according to which the glass state is destroyed owing to the increased density of phonon states. Keeping to our reasoning, we conclude that the orientational glass state does not disappear but, instead, is conserved almost unchanged under one-molecule feeling and persists to appreciably higher temperatures in the case of double filling, which affects exciton dynamics stronger.